Hydrogen-containing amorphous carbon film with long wear life and preparation method thereof

By using vacuum magnetron sputtering technology to deposit a multilayer structure in hydrogen-containing amorphous carbon (a-C:H) films, the problem of hydrogen atom desorption during friction and wear is solved, and low friction coefficient and long wear are achieved. Take into account lifespan.

CN119465051AActive Publication Date: 2025-02-18LANZHOU INST OF PHYSICS CHINESE ACADEMY OF SPACE TECH

Patent Information

Application Number
CN202411593201.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

Existing hydrogen-containing amorphous carbon (a-C:H) films are prone to desorption during friction and wear, resulting in an increase in friction coefficient and a shortening of wear life.

Method used

Using vacuum magnetron sputtering technology, Ti transition layer, TiN hydrogen resistance layer, TiCHx hydrogen storage layer, Ti/C/H transition layer and hydrogen-containing a-C layer are deposited on the substrate surface from bottom to top, and hydrogen-containing a-C layer is achieved through the combination of these layers. Fix and store to extend the wear life of the film.

Benefits of technology

It achieves a balance between low friction coefficient and long wear life in a vacuum environment, ensuring the stable performance of the film during friction and wear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465051A_ABST
    Figure CN119465051A_ABST
Patent Text Reader

Abstract

The invention provides a hydrogen-containing amorphous carbon film with long wear life and a preparation method thereof, and belongs to the field of composite material preparation. The a-C: H thin film with the long wear life comprises a substrate, and a Ti transition layer, a TiN hydrogen resistance layer, a TiCHx hydrogen storage layer, a Ti / C / H transition layer and a hydrogen-containing a-C layer which are formed on the surface of the substrate from bottom to top. Through connection transition between the Ti transition layer and the metal substrate, strong combination between the hydrogen-containing DLC film and the metal substrate is realized. By depositing the TiN hydrogen blocking layer, hydrogen atoms in the TiCHx hydrogen storage layer are prevented from diffusing and losing towards the direction of the substrate. By depositing the TiCHx hydrogen storage layer, hydrogen atoms are fixed and stored by using the hydrogen storage characteristic of Ti, and the hydrogen atoms are provided for the surface hydrogen-containing a-C layer in the working process of the thin film. By depositing the Ti / C transition layer, connection transition between the TiCHx hydrogen storage layer and the hydrogen-containing a-C layer is achieved, compatibility is improved, and good combination is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite material preparation, and in particular to a hydrogenated amorphous carbon film with a long wear life and a preparation method thereof. Background Art

[0002] Hydrogenated amorphous carbon (aC:H) film is a hydrogenated diamond-like carbon (DLC) film composed of sp 2 C and sp 3 It is composed of carbon atoms and hydrogen atoms combined with C. As a new type of lubricating film material, it has the characteristics of small vacuum friction coefficient, good chemical stability, and strong corrosion resistance. It is widely used in machinery, electronics, optics, thermal, acoustics, medicine and other fields.

[0003] In a vacuum environment, hydrogen atoms can passivate the carbon atom dangling bonds on the surface of hydrogen-containing DLC ​​films, so the presence of hydrogen provides a certain lubrication ability, allowing it to be used in some scenarios that require reduced friction and wear. However, during the friction and wear process, hydrogen atoms are easily desorbed under the influence of thermal effects, and the carbon atom surface dangling bonds are exposed, resulting in increased adhesion between the film and the friction pair, increased friction coefficient, and shortened wear life. Therefore, how to ensure that a low friction coefficient is maintained while preparing aC:H film with a long wear life becomes a challenge. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the life problem of hydrogenated amorphous carbon (aC:H) films in the prior art and provide a hydrogenated amorphous carbon (aC:H) film with a long wear life and a preparation method thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A hydrogenated amorphous carbon (aC:H) film with long wear life, comprising a substrate, a Ti transition layer, a TiN hydrogen barrier layer, a TiCH x Hydrogen storage layer (x = 0.5 ~ 1), Ti / C / H transition layer and hydrogen-containing aC layer;

[0007] The Ti transition layer is formed on the surface of the substrate by vacuum magnetron sputtering technology;

[0008] The TiN hydrogen barrier layer is formed on the surface of the Ti transition layer by vacuum magnetron sputtering technology;

[0009] The TiCH x The hydrogen storage layer is formed on the surface of the TiN hydrogen barrier layer by vacuum magnetron sputtering technology;

[0010] The Ti / C / H transition layer in TiCH xThe surface of the hydrogen storage layer is prepared by vacuum magnetron sputtering technology;

[0011] The hydrogen-containing aC layer is prepared on the surface of the Ti / C / H transition layer by vacuum magnetron sputtering technology.

[0012] The total thickness of the film is 2.00-2.30 μm;

[0013] The friction coefficient of the film in a vacuum environment is less than 0.02;

[0014] The substrate is a metal substrate.

[0015] A method for preparing a hydrogenated amorphous carbon film with a long wear life comprises the following steps:

[0016] Step (1), pre-treating the substrate;

[0017] Step (2), preparing a Ti transition layer on the surface of the pretreated substrate using vacuum magnetron sputtering technology;

[0018] Step (3), preparing a TiN hydrogen barrier layer on the surface of the Ti transition layer by using vacuum magnetron sputtering technology;

[0019] Step (4), using vacuum magnetron sputtering technology to prepare TiCH on the surface of the TiN hydrogen barrier layer x Hydrogen storage layer;

[0020] Step (5), using vacuum magnetron sputtering technology to deposit the TiCH x Preparation of Ti / C / H transition layer on the surface of hydrogen storage layer;

[0021] Step (6), preparing a hydrogen-containing aC layer on the surface of the Ti / C / H transition layer using vacuum magnetron sputtering technology.

[0022] In the step (1), the method for pretreating the substrate is: grinding and polishing the surface of the substrate, then cleaning it in an acetone solution and an alcohol solution in sequence, drying it, and finally bombarding the surface of the substrate with a cation layer ion source under vacuum conditions to remove impurities and an oxide layer;

[0023] The method of bombarding the surface of the substrate with a positive layer ion source under vacuum conditions is as follows: placing the cleaned and dried substrate into a vacuum chamber, fixing it on a workpiece rack, and evacuating the vacuum chamber so that the vacuum degree is 5×10 - 3Pa, heat the vacuum chamber to 190-210°C, turn on the cation layer ion source to bombard the surface of the substrate, the cation layer ion beam source voltage is 1500V, introduce argon gas into the vacuum chamber, the chamber vacuum degree is 0.1-1Pa, the substrate pressure is -200V, and the cleaning time is 1800s.

[0024] In the step (2), the method of preparing a Ti transition layer on the surface of the substrate using vacuum magnetron sputtering technology is as follows: power is applied to the Ti target, the Ti target power is 5 kW, the argon gas flow rate is gradually increased from 0 to 700 sccm, the substrate bias is -50 V, and the deposition time is 180 s.

[0025] In the step (3), the method of preparing a TiN hydrogen barrier layer on the surface of the Ti transition layer using vacuum magnetron sputtering technology is as follows: after the Ti transition layer is prepared, nitrogen is introduced into the vacuum chamber, the nitrogen flow rate is gradually increased from 0 to 100 sccm, the argon flow rate is gradually reduced from 700 sccm to 600 sccm, the gas pressure is 0.5-1 Pa, the Ti power is 5 kW, the substrate bias is -80 V, and the deposition time is 900 s.

[0026] In the step (4), vacuum magnetron sputtering technology is used to prepare TiCH on the surface of the TiN hydrogen barrier layer. x The method for the hydrogen storage layer is as follows: after the TiN hydrogen barrier layer is prepared, acetylene gas is introduced into the vacuum chamber, the acetylene gas flow rate is gradually increased from 0 to 100 sccm, the argon gas flow rate is maintained at 600 sccm, the gas pressure is 0.5-1 Pa, the Ti target power is 6 kW, the substrate bias is -100 V, and the deposition time is 1200 s.

[0027] In the step (5), vacuum magnetron sputtering technology is used to deposit the TiCH x The method for preparing the Ti / C / H transition layer on the surface of the hydrogen storage layer is: TiCH x After the hydrogen storage layer is prepared, acetylene gas is introduced into the vacuum chamber, the acetylene gas flow rate is gradually increased from 0 to 200 sccm, the argon gas flow rate is gradually reduced from 600 sccm to 500 sccm, the gas pressure is 0.5-1 Pa, the Ti target power is 2 kW, the substrate bias is -100 V, and the deposition time is 360 s.

[0028] In the step (6), the method of preparing the hydrogen-containing aC layer on the surface of the Ti / C / H transition layer by using vacuum magnetron sputtering technology is as follows: after the Ti / C / H transition layer is prepared, acetylene gas is introduced into the vacuum chamber, the acetylene gas flow rate is maintained at 200sccm, the argon gas flow rate is maintained at 500sccm, the gas pressure is 0.5-1Pa, the graphite target power is 2kW, the substrate bias is -150V, and the deposition time is 1800s.

[0029] The technical solution of the present invention has the following advantages:

[0030] The present invention provides a hydrogen-containing amorphous carbon (aC:H) film with long wear life and a preparation method thereof, belonging to the field of composite material preparation. The long wear life aC:H film comprises a substrate, and a Ti transition layer, a TiN hydrogen barrier layer, a TiCH x Hydrogen storage layer, Ti / C / H transition layer and hydrogen-containing aC layer. Ti transition layer, TiN hydrogen barrier layer, TiCH x The hydrogen storage layer, Ti / C / H transition layer and hydrogen-containing aC layer are all deposited by vacuum magnetron sputtering technology. Through the connection transition between the Ti transition layer and the metal substrate, a strong bond between the hydrogen-containing DLC ​​film and the metal substrate is achieved. By depositing the TiN hydrogen barrier layer, the TiCH x The hydrogen atoms in the hydrogen storage layer diffuse and lose toward the substrate. x The hydrogen storage layer uses the hydrogen storage properties of Ti to fix and store hydrogen atoms, and provides hydrogen atoms to the surface hydrogen-containing aC layer during the film operation. By depositing a Ti / C transition layer, TiCH x The connection transition between the hydrogen storage layer and the hydrogen-containing aC layer improves compatibility and achieves good bonding. The hydrogen-containing aC layer is deposited using vacuum magnetron sputtering technology, so that the carbon atoms of the hydrogen-containing aC layer are mainly sp 2 Hybrid bond combination increases the proportion of graphite-like carbon; hydrogen atoms in the film can passivate the dangling bonds of carbon atoms on the surface of the aC:H film, TiH x The hydrogen atoms in the hydrogen storage layer can replenish the loss of the aC:H film when working in a vacuum environment, thereby continuously passivating the dangling bonds of surface carbon atoms and achieving a long wear life.

[0031] In the hydrogenated amorphous carbon (aC:H) film with a long wear life provided by the present invention, a strong bond between the hydrogenated DLC film and the metal substrate is achieved through the connection transition between the Ti transition layer and the metal substrate. By depositing the TiN hydrogen barrier layer, the TiCH x The hydrogen atoms in the hydrogen storage layer diffuse and lose toward the substrate. x The hydrogen storage layer uses the hydrogen storage properties of Ti to fix and store hydrogen atoms, and provides hydrogen atoms to the surface hydrogen-containing aC layer during the film operation. By depositing a Ti / C transition layer, TiCH x The connection transition between the hydrogen storage layer and the hydrogen-containing aC layer improves compatibility and achieves good bonding. The hydrogen-containing aC layer is deposited using vacuum magnetron sputtering technology, so that the carbon atoms of the hydrogen-containing aC layer are mainly sp 2 Hybrid bond combination increases the proportion of graphite-like carbon; hydrogen atoms in the film can passivate the dangling bonds of carbon atoms on the surface of the aC:H film, TiHx The hydrogen atoms in the hydrogen storage layer can replenish the loss of the aC:H film when working in a vacuum environment, thereby continuously passivating the dangling bonds of surface carbon atoms and achieving a long wear life. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 Schematic diagram of the structure of aC:H film with long wear life;

[0034] Figure 2 Schematic diagram of the preparation method of aC:H film with long wear life;

[0035] Figure 3 Schematic diagram of transmission electron microscopy of aC:H film with long wear life;

[0036] Figure 4 Vacuum tribology test curve of aC:H film with long wear life;

[0037] Reference numerals: 1-substrate; 2-Ti transition layer; 3-TiN hydrogen barrier layer; 4-TiCH x Hydrogen storage layer; 5-Ti / C / H transition layer; 6-hydrogen-containing aC layer; 7-workpiece holder; 8-magnetron sputtering graphite target; 9-anode layer ion source height; 10-magnetron sputtering Ti target; 11-heating wire. DETAILED DESCRIPTION

[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. The raw materials or instruments used are all conventional products that can be obtained commercially, including but not limited to the raw materials or instruments used in the examples of this application.

[0040] The following will be combined with the attached Figure 1 and attached Figure 2, a hydrogenated amorphous carbon (aC:H) film with a long wear life and a preparation method thereof provided in an embodiment of the present application are introduced in detail.

[0041] See also Figure 1 , the present application embodiment provides a schematic diagram of the structure of a hydrogenated amorphous carbon (aC:H) film with a long wear life. Figure 1 As shown, the hydrogenated amorphous carbon (aC:H) film with a long wear life in the embodiment of the present application comprises: a substrate 1, a Ti transition layer 2, a TiN hydrogen barrier layer 3, a TiCH x Hydrogen storage layer 4, Ti / C / H transition layer 5, hydrogen-containing aC layer 6. Among them, the Ti transition layer 2 is on the surface of the substrate 1, the TiN hydrogen barrier layer 3 is on the surface of the Ti transition layer 2, and the TiCH x The hydrogen storage layer 4 is on the surface of the TiN hydrogen barrier layer 3, and the Ti / C / H transition layer 5 is on the surface of the TiCH x The surface of the hydrogen storage layer 4 and the hydrogen-containing aC layer 6 are on the surface of the Ti / C / H transition layer 5 .

[0042] See also Figure 2 , the present application embodiment provides a schematic diagram of a method for preparing a hydrogenated amorphous carbon (aC:H) film with a long wear life. Figure 2 As shown, the preparation of the hydrogenated amorphous carbon (aC:H) film with a long wear life in the embodiment of the present application is carried out in a vacuum chamber. A workpiece rack 7 is arranged in the center of the vacuum chamber for fixing the workpiece to be processed; the vacuum chamber has 8 sides, on which magnetron sputtering graphite targets 8 (for depositing hydrogenated aC layers), anode layer ion sources 9 (for cleaning metal substrates), magnetron sputtering Ti targets 10 (for depositing Ti transition layers, TiN hydrogen barrier layers, TiCH x Hydrogen storage layer and Ti / C / H transition layer) and heating wire 11 (for heating the vacuum chamber).

[0043] Example 1

[0044] This embodiment provides a hydrogenated amorphous carbon (aC:H) film with a long wear life, comprising: a 9Cr18 stainless steel substrate, a Ti transition layer, a TiN hydrogen barrier layer, a TiCH x Hydrogen storage layer, Ti / C / H transition layer and hydrogen-containing aC layer; the specific steps are as follows:

[0045] (1) Substrate pretreatment;

[0046] A 9Cr18 stainless steel substrate was selected and first ground and polished to a surface roughness less than Ra 0.8. Then, it was ultrasonically cleaned in an acetone solution for 10 min, then cleaned in an alcohol solution for 10 min, and then dried in a drying oven at 70 °C for 20 min. The substrate after cleaning and drying was placed in a vacuum chamber and fixed on a workpiece rack. The vacuum chamber was evacuated to a vacuum degree of 5 × 10 -3 Pa, heat the vacuum chamber to 200°C, turn on the cation layer ion source to bombard the surface of the substrate, the cation layer ion beam source voltage is 1500V, introduce argon gas into the vacuum chamber, the chamber vacuum degree is 0.1~1Pa, the substrate pressure is -200V, and the cleaning time is 1800s.

[0047] (2) preparing a Ti transition layer on the surface of the substrate using vacuum magnetron sputtering technology;

[0048] The vacuum degree of the vacuum chamber is better than 5×10 -3 Pa, power was applied to the Ti target, vacuum magnetron sputtering deposition was performed on the substrate surface, the Ti target power was 5 kW, the argon flow rate was gradually increased from 0 to 700 sccm, the substrate bias was -50 V, the deposition time was 180 s, and a Ti transition layer was formed;

[0049] (3) A TiN hydrogen barrier layer is prepared on the surface of the Ti transition layer using vacuum magnetron sputtering technology;

[0050] Nitrogen gas is introduced into the vacuum chamber, the nitrogen flow rate is gradually increased from 0 to 100 sccm, the argon flow rate is gradually reduced from 700 sccm to 600 sccm, the gas pressure is 0.5-1 Pa, the Ti power is 5 kW, the substrate bias is -80 V, and the deposition time is 900 s to form a TiN hydrogen barrier layer;

[0051] (4) Preparation of TiCH on the surface of TiN hydrogen barrier layer using vacuum magnetron sputtering technology x Hydrogen storage layer;

[0052] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was gradually increased from 0 to 100 sccm, the argon gas flow rate was maintained at 600 sccm, the gas pressure was 0.5-1 Pa, the Ti target power was 6 kW, the substrate bias voltage was -100 V, and the deposition time was 1200 s to form TiCH x Hydrogen storage layer.

[0053] (5) Using vacuum magnetron sputtering technology on TiCH x Preparation of Ti / C / H transition layer on the surface of hydrogen storage layer;

[0054] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was gradually increased from 0 to 200 sccm, the argon gas flow rate was gradually reduced from 600 sccm to 500 sccm, the gas pressure was 0.5-1 Pa, the Ti target power was 2 kW, the substrate bias was -100 V, the deposition time was 360 s, and a Ti / C / H transition layer was formed.

[0055] (6) using vacuum magnetron sputtering technology to prepare a hydrogen-containing aC layer on the surface of the Ti / C / H transition layer;

[0056] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was maintained at 200 sccm, the argon gas flow rate was maintained at 500 sccm, the gas pressure was 0.5-1 Pa, the graphite target power was 2 kW, the substrate bias was -150 V, the deposition time was 1800 s, and a hydrogen-containing aC layer was formed.

[0057] (7) stopping the deposition of the coating until the temperature of the vacuum chamber is lower than 80° C., taking out the substrate, and obtaining a hydrogenated amorphous carbon (aC:H) film with a long wear life.

[0058] The obtained transmission electron microscopy images of hydrogenated amorphous carbon (aC:H) films with long wear life are shown in Figure 2. Figure 3 As shown, the vacuum tribology test curve is as follows Figure 4 shown.

[0059] Example 2

[0060] The present embodiment provides a hydrogenated amorphous carbon (aC:H) film with a long wear life, comprising: a cemented carbide substrate, a Ti transition layer, a TiN hydrogen barrier layer, a TiCH x Hydrogen storage layer, Ti / C / H transition layer and hydrogen-containing aC layer;

[0061] The specific steps are as follows:

[0062] (1) Substrate pretreatment;

[0063] A cemented carbide substrate was selected, first ground and polished to a surface roughness less than Ra 0.8, then placed in an acetone solution for ultrasonic cleaning for 10 min, then cleaned in an alcohol solution for 10 min, and then dried in a drying oven at a temperature of 70 ° C for 20 min. The substrate after cleaning and drying was placed in a vacuum chamber, fixed on a workpiece rack, and evacuated to a vacuum degree of 5 × 10 -3 Pa, heat the vacuum chamber to 210°C, turn on the cation layer ion source to bombard the surface of the substrate, the cation layer ion beam source voltage is 1500V, introduce argon gas into the vacuum chamber, the chamber vacuum degree is 0.1~1Pa, the substrate pressure is -200V, and the cleaning time is 1800s.

[0064] (2) preparing a Ti transition layer on the surface of the substrate using vacuum magnetron sputtering technology;

[0065] The vacuum degree of the vacuum chamber is better than 5×10 -3 Pa, power was applied to the Ti target, vacuum magnetron sputtering deposition was performed on the substrate surface, the Ti target power was 5 kW, the argon flow rate was gradually increased from 0 to 700 sccm, the substrate bias was -50 V, the deposition time was 180 s, and a Ti transition layer was formed;

[0066] (3) A TiN hydrogen barrier layer is prepared on the surface of the Ti transition layer using vacuum magnetron sputtering technology;

[0067] Nitrogen gas is introduced into the vacuum chamber, the nitrogen flow rate is gradually increased from 0 to 100 sccm, the argon flow rate is gradually reduced from 700 sccm to 600 sccm, the gas pressure is 0.5-1 Pa, the Ti power is 5 kW, the substrate bias is -80 V, and the deposition time is 900 s to form a TiN hydrogen barrier layer;

[0068] (4) Preparation of TiCH on the surface of TiN hydrogen barrier layer using vacuum magnetron sputtering technology x Hydrogen storage layer;

[0069] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was gradually increased from 0 to 100 sccm, the argon gas flow rate was maintained at 600 sccm, the gas pressure was 0.5-1 Pa, the Ti target power was 6 kW, the substrate bias voltage was -100 V, and the deposition time was 1200 s to form TiCH x Hydrogen storage layer.

[0070] (5) Using vacuum magnetron sputtering technology on TiCH x Preparation of Ti / C / H transition layer on the surface of hydrogen storage layer;

[0071] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was gradually increased from 0 to 200 sccm, the argon gas flow rate was gradually reduced from 600 sccm to 500 sccm, the gas pressure was 0.5-1 Pa, the Ti target power was 2 kW, the substrate bias was -100 V, the deposition time was 360 s, and a Ti / C / H transition layer was formed.

[0072] (6) using vacuum magnetron sputtering technology to prepare a hydrogen-containing aC layer on the surface of the Ti / C / H transition layer;

[0073] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was maintained at 200 sccm, the argon gas flow rate was maintained at 500 sccm, the gas pressure was 0.5-1 Pa, the graphite target power was 2 kW, the substrate bias was -150 V, the deposition time was 1800 s, and a hydrogen-containing aC layer was formed.

[0074] (7) stopping the deposition of the coating until the temperature of the vacuum chamber is lower than 80° C., taking out the substrate, and obtaining a hydrogenated amorphous carbon (aC:H) film with a long wear life.

[0075] Example 3

[0076] The present embodiment provides a hydrogenated amorphous carbon (aC:H) film with a long wear life, comprising: a high-speed steel substrate, a Ti transition layer, a TiN hydrogen barrier layer, a TiCH x Hydrogen storage layer, Ti / C / H transition layer and hydrogen-containing aC layer;

[0077] The specific steps are as follows:

[0078] (1) Substrate pretreatment;

[0079] A high-speed steel substrate was selected, ground and polished to a surface roughness less than Ra 0.8, then ultrasonically cleaned in an acetone solution for 10 min, then cleaned in an alcohol solution for 10 min, and then dried in a drying oven at 70 °C for 20 min. The substrate after cleaning and drying was placed in a vacuum chamber, fixed on a workpiece rack, and evacuated to a vacuum degree of 5 × 10 -3 Pa, heat the vacuum chamber to 190-210°C, turn on the cation layer ion source to bombard the surface of the substrate, the cation layer ion beam source voltage is 1500V, introduce argon gas into the vacuum chamber, the chamber vacuum degree is 0.6Pa, the substrate pressure is -200V, and the cleaning time is 1800s.

[0080] (2) preparing a Ti transition layer on the surface of the substrate using vacuum magnetron sputtering technology;

[0081] The vacuum degree of the vacuum chamber is better than 5×10 -3 Pa, power was applied to the Ti target, vacuum magnetron sputtering deposition was performed on the substrate surface, the Ti target power was 5 kW, the argon flow rate was gradually increased from 0 to 700 sccm, the substrate bias was -50 V, the deposition time was 180 s, and a Ti transition layer was formed;

[0082] (3) A TiN hydrogen barrier layer is prepared on the surface of the Ti transition layer using vacuum magnetron sputtering technology;

[0083] Nitrogen gas is introduced into the vacuum chamber, the nitrogen flow rate is gradually increased from 0 to 100 sccm, the argon flow rate is gradually reduced from 700 sccm to 600 sccm, the gas pressure is 0.5-1 Pa, the Ti power is 5 kW, the substrate bias is -80 V, and the deposition time is 900 s to form a TiN hydrogen barrier layer;

[0084] (4) Preparation of TiCH on the surface of TiN hydrogen barrier layer using vacuum magnetron sputtering technology x Hydrogen storage layer;

[0085] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was gradually increased from 0 to 100 sccm, the argon gas flow rate was maintained at 600 sccm, the gas pressure was 0.5-1 Pa, the Ti target power was 6 kW, the substrate bias voltage was -100 V, and the deposition time was 1200 s to form TiCH x Hydrogen storage layer.

[0086] (5) Using vacuum magnetron sputtering technology on TiCH x Preparation of Ti / C / H transition layer on the surface of hydrogen storage layer;

[0087] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was gradually increased from 0 to 200 sccm, the argon gas flow rate was gradually reduced from 600 sccm to 500 sccm, the gas pressure was 0.5-1 Pa, the Ti target power was 2 kW, the substrate bias was -100 V, the deposition time was 360 s, and a Ti / C / H transition layer was formed.

[0088] (6) using vacuum magnetron sputtering technology to prepare a hydrogen-containing aC layer on the surface of the Ti / C / H transition layer;

[0089] Acetylene gas was introduced into the vacuum chamber, the acetylene gas flow rate was maintained at 200 sccm, the argon gas flow rate was maintained at 500 sccm, the gas pressure was 0.5-1 Pa, the graphite target power was 2 kW, the substrate bias was -150 V, the deposition time was 1800 s, and a hydrogen-containing aC layer was formed.

[0090] (7) stopping the deposition of the coating until the temperature of the vacuum chamber is lower than 80° C., taking out the substrate, and obtaining a hydrogenated amorphous carbon (aC:H) film with a long wear life.

[0091] The physicochemical properties of the hydrogenated amorphous carbon (aC:H) films with long wear life prepared in Examples 1 to 3 of the present application were tested.

[0092] Friction coefficient test under vacuum environment: The tribological properties of the samples were tested using a vacuum ball-on-disc friction tester. The friction pair was a 9Cr18 steel ball with a diameter of 8 mm. The test conditions were: load 5 N, friction radius 8 mm, rotation speed 500 r / min, and number of revolutions 1000 r.

[0093] Wear life test under vacuum environment: The tribological performance of the sample was tested using a vacuum ball-on-disc friction tester. The friction pair was a 9Cr18 steel ball with a diameter of 8 mm. The test conditions were: load 5N, friction radius 8mm, and rotation speed 500r / min.

[0094] The physical and chemical properties test results of the hydrogenated amorphous carbon (aC:H) films with long wear life prepared in Examples 1 to 3 are shown in Table 1.

[0095] Table 1

[0096] Example Total thickness Friction coefficient in vacuum environment Wear life in vacuum environment Wear rate in vacuum environment 1 2.10μm 0.015 <![CDATA[4.5×10 5 Transfer]]> <![CDATA[8.2×10 -17 mm 3 / Nm <!-- 6 -->]]> 2 2.16μm 0.011 <![CDATA[5.1×10 5 Transfer]]> <![CDATA[7.4×10 -17 mm 3 / Nm]]> 3 2.21μm 0.012 <![CDATA[4.8×10 5 Transfer]]> <![CDATA[6.8×10 -17 mm 3 / Nm]]> Comparative Example 1 1.60μm 0.017 <![CDATA[5.5×10 3 Transfer]]> <![CDATA[6.5×10 -15 mm 3 / Nm]]> Comparative Example 2 2.20μm 0.010 <![CDATA[2.3×10 4 Transfer]]> <![CDATA[3.2×10 -16 mm 3 / Nm]]>

[0097] The test results show that the total thickness of the hydrogenated amorphous carbon (aC:H) film with long wear life prepared in Examples 1 to 3 of the present application is 2.00 to 2.30 μm, and the friction coefficient under vacuum is less than 0.02. Comparative Example 1 is a conventional hydrogenated amorphous carbon (aC:H) film prepared by vacuum magnetron sputtering. Although it has a small friction coefficient under vacuum, it has a short wear life and a high wear rate under vacuum, and cannot work stably for a long time under vacuum. Comparative Example 2 is a hydrogenated amorphous carbon (aC:H) film prepared by conventional plasma enhanced vacuum magnetron sputtering deposition. Although it has good tribological properties, its wear life under vacuum is short. The hydrogenated amorphous carbon (aC:H) film with long wear life prepared in Examples 1 to 3 has a significantly higher wear life under vacuum than Comparative Example 2, and also has good tribological properties under vacuum. It can be seen that the hydrogenated amorphous carbon (aC:H) films with long wear life prepared in Examples 1 to 3 exhibit excellent long wear life under the premise of having a relatively low friction coefficient in a vacuum environment, showing good comprehensive performance and will certainly be suitable for more demanding operating conditions.

[0098] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A hydrogenated amorphous carbon film with long wear life, characterized in that: The film includes a substrate, a Ti transition layer, a TiN hydrogen barrier layer, a TiCH x Hydrogen storage layer, Ti / C / H transition layer and hydrogen-containing aC layer; The Ti transition layer is formed on the surface of the substrate by vacuum magnetron sputtering technology; The TiN hydrogen barrier layer is formed on the surface of the Ti transition layer by vacuum magnetron sputtering technology; The TiCH x The hydrogen storage layer is formed on the surface of the TiN hydrogen barrier layer by vacuum magnetron sputtering technology; The Ti / C / H transition layer in TiCH x The surface of the hydrogen storage layer is prepared by vacuum magnetron sputtering technology; The hydrogen-containing aC layer is prepared on the surface of the Ti / C / H transition layer by vacuum magnetron sputtering technology.

2. The hydrogenated amorphous carbon film with long wear life according to claim 1, characterized in that: The substrate is a metal substrate.

3. A hydrogenated amorphous carbon film with a long wear life according to claim 1 or 2, characterized in that: The total thickness of the film is 2.00-2.30 μm; The friction coefficient of the film in a vacuum environment is less than 0.

02.

4. A method for preparing a hydrogenated amorphous carbon film having a long wear life, characterized in that Corrections to this approach include: Step (1), pre-treating the substrate; Step (2), preparing a Ti transition layer on the surface of the pretreated substrate using vacuum magnetron sputtering technology; Step (3), preparing a TiN hydrogen barrier layer on the surface of the Ti transition layer by using vacuum magnetron sputtering technology; Step (4), using vacuum magnetron sputtering technology to prepare TiCH on the surface of the TiN hydrogen barrier layer x Hydrogen storage layer; Step (5), using vacuum magnetron sputtering technology to deposit the TiCH x Preparation of Ti / C / H transition layer on the surface of hydrogen storage layer; Step (6), preparing a hydrogen-containing aC layer on the surface of the Ti / C / H transition layer using vacuum magnetron sputtering technology.

5. The method for preparing a hydrogenated amorphous carbon film with a long wear life according to claim 4, characterized in that: In the step (1), the method for pretreating the substrate is: grinding and polishing the surface of the substrate, then cleaning it in an acetone solution and an alcohol solution in sequence, drying it, and finally bombarding the surface of the substrate with a cation layer ion source under vacuum conditions to remove impurities and an oxide layer; The method of bombarding the surface of the substrate with a positive layer ion source under vacuum conditions is as follows: placing the cleaned and dried substrate into a vacuum chamber, fixing it on a workpiece rack, and evacuating the vacuum chamber so that the vacuum degree is 5×10 -3 Pa, heat the vacuum chamber to 190-210°C, turn on the cation layer ion source to bombard the surface of the substrate, the cation layer ion beam source voltage is 1500V, introduce argon gas into the vacuum chamber, the chamber vacuum degree is 0.1-1Pa, the substrate pressure is -200V, and the cleaning time is 1800s.

6. A method for preparing a hydrogenated amorphous carbon film with a long wear life according to claim 4 or 5, characterized in that: In the step (2), the method of preparing a Ti transition layer on the surface of the substrate using vacuum magnetron sputtering technology is as follows: power is applied to the Ti target, the Ti target power is 5 kW, the argon gas flow rate is gradually increased from 0 to 700 sccm, the substrate bias voltage is -50 V, and the deposition time is 180 s.

7. The method for preparing a hydrogenated amorphous carbon film with a long wear life according to claim 4, characterized in that: In the step (3), the method of preparing a TiN hydrogen barrier layer on the surface of the Ti transition layer using vacuum magnetron sputtering technology is as follows: after the Ti transition layer is prepared, nitrogen is introduced into the vacuum chamber, the nitrogen flow rate is gradually increased from 0 to 100 sccm, the argon flow rate is gradually reduced from 700 sccm to 600 sccm, the gas pressure is 0.5-1 Pa, the Ti power is 5 kW, the substrate bias is -80 V, and the deposition time is 900 s.

8. The method for preparing a hydrogenated amorphous carbon film with a long wear life according to claim 4, characterized in that: In the step (4), vacuum magnetron sputtering technology is used to prepare TiCH on the surface of the TiN hydrogen barrier layer. x The method for the hydrogen storage layer is as follows: after the TiN hydrogen barrier layer is prepared, acetylene gas is introduced into the vacuum chamber, the acetylene gas flow rate is gradually increased from 0 to 100 sccm, the argon gas flow rate is maintained at 600 sccm, the gas pressure is 0.5-1 Pa, the Ti target power is 6 kW, the substrate bias is -100 V, and the deposition time is 1200 s.

9. The method for preparing a hydrogenated amorphous carbon film with a long wear life according to claim 4, characterized in that: In the step (5), vacuum magnetron sputtering technology is used to deposit the TiCH x The method for preparing the Ti / C / H transition layer on the surface of the hydrogen storage layer is: TiCH x After the hydrogen storage layer is prepared, acetylene gas is introduced into the vacuum chamber, the acetylene gas flow rate is gradually increased from 0 to 200 sccm, the argon gas flow rate is gradually reduced from 600 sccm to 500 sccm, the gas pressure is 0.5-1 Pa, the Ti target power is 2 kW, the substrate bias is -100 V, and the deposition time is 360 s.

10. The method for preparing a hydrogenated amorphous carbon film with a long wear life according to claim 4, characterized in that: In the step (6), the method of preparing the hydrogen-containing aC layer on the surface of the Ti / C / H transition layer by using vacuum magnetron sputtering technology is as follows: after the Ti / C / H transition layer is prepared, acetylene gas is introduced into the vacuum chamber, the acetylene gas flow rate is maintained at 200sccm, the argon gas flow rate is maintained at 500sccm, the gas pressure is 0.5-1Pa, the graphite target power is 2kW, the substrate bias is -150V, and the deposition time is 1800s.

Citation Information

Patent Citations

  • Ultra-hard carbon film and preparation method thereof

    CN101554790A

  • Multilayer composite diamond-like film material and preparation method thereof

    CN108977766A

  • Preparation of fullerene / amorphous carbon-hydrogen composite film and application to vacuum low-temperature environment

    CN111455315A

  • Super-lubricity performance metal / hydrogen-containing carbon composite thin film and preparation method thereof

    CN111850470A

  • Space wear-resistant lubricating composite structure film and preparation method thereof

    CN116815144A

Cited By

  • Preparation method and application of titanium-based hydrogen-resistant coating structure on surface of metal hydride

    CN121228190A

  • A preparation method and application of a metal hydride surface titanium-based hydrogen barrier coating structure

    CN121228190B

  • Low-wear hydrogen-containing amorphous carbon film based on hydrogen-mediated interface stability and preparation and application thereof

    CN121874739A